Preparation of MOF-Modified Nitrogen-Phosphorus Flame Retardant and Its Application in Polyester

By using a flame retardant system combining N and P flame retardants with MOFs compounds in polyester, the problems of more melt droplets, low oxygen index and large smoke during burning of polyester are solved, and the effects of no melt droplets, low smoke, high oxygen index and anti-pilling are achieved.

CN117026632BActive Publication Date: 2025-06-24YANTAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310989531.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-06-24
Estimated Expiration
2043-08-07

AI Technical Summary

Technical Problem

Polyester produces multiple melt droplets during combustion, causing secondary harm, low oxygen index and large amounts of smoke, making it easy to pill during use.

Method used

The N and P flame retardant combined with MOFs compound system is used to improve the flame retardant carbon property and flame retardant oxygen index, reduce the combustion droplets, and at the same time, the lubricity of esters and ammonium persulfate are used as initiators to modify the polymer amino group through ethylenediaminetetraacetic acid, so that the MOFs modified nitrogen and phosphorus flame retardant is complexed with the carboxy group to prevent pilling.

Benefits of technology

The production of melt-free droplets is achieved, the oxygen index is improved, the smoke is greatly reduced, and the flame retardancy and heat resistance of polyester are significantly improved, preventing pilling and extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the preparation of MOF-modified nitrogen-phosphorus flame retardants and their application in polyester. Pentaerythritol phosphate ester is obtained by reacting pentaerythritol with a phosphorus-based compound, and is modified with a phosphorus-chlorine compound and ethanolamine to obtain a nitrogen-phosphorus flame retardant. The nitrogen-phosphorus flame retardant is reacted with a MOF product to obtain a MOF-modified nitrogen-phosphorus flame retardant, which is used in a flame retardant finishing solution for polyester finishing. The obtained polyester has the characteristics of high oxygen index, few melt drops and little smoke, and the oxygen index decreases slightly after 50 washes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation of MOFs-modified nitrogen-phosphorus flame retardants, and particularly to the preparation of MOFs-modified nitrogen-phosphorus flame retardants and their application in polyester. Background Art

[0002] There are generally two ways to flame-retardant treat polyester. One is to blend a flame retardant with polyester chips for spinning to obtain the flame-retardant polyester. The other is to conduct flame-retardant finishing on polyester to improve its flame retardancy.

[0003] Chinese Patent Invention CN202210521614.9 relates to a preparation method of a highly elastic flame-retardant polyester fabric. First is the synthesis process of the flame retardant. This application relates to the technical field of textile products. The raw materials used are PET, cellulose fiber, nano-aluminum trioxide, glycerol, PEG-400 parts, and a flame retardant. The flame retardant raw materials are synthesized from cyclic phosphate ester, ultrafine ammonium polyphosphate, and pentaerythritol. The limiting oxygen index and char residue of the polyester fabric are 39% and 34% respectively. The limiting oxygen index value of the polyester fabric has indeed been improved, but there is still a large room for improvement in its char yield. It uses a flame retardant and polyester raw materials for melt droplet spinning. Although the oxygen index is relatively high, there is no improvement in the melt droplet aspect, and the disadvantages are that the process is slightly complex and the development cost of the copolymer flame retardant is high.

[0004] Chinese Patent Invention CN202110520184.4 relates to a synthesis process of a flame retardant. A finishing solution is prepared and used to soak polyester textiles to increase the flame retardancy of the polyester textiles. This flame retardant is prepared from dimethyl phenylphosphonate, ethylene glycol, and polyethylene glycol as raw materials, with zinc acetate and antimony trioxide as composite catalysts, and heated under a nitrogen atmosphere protection to obtain a durable flame retardant for polyester. For its vertical burning test, it is tested with reference to "GT / T5455-1997 Textiles - Burning Performance - Vertical Method". Before the flame retardant treatment, the polyester completely burns. After the flame retardant treatment, the shortest damaged carbon length after vertical burning is 12.8 cm, and both the afterflame time and the smoldering time are 0, showing relatively good self-extinguishing properties, but it does not solve the defects of melt dripping during combustion and low oxygen index.

[0005] In the previous work of our team, Wang Qiyan used pentaerythritol as the carbon source and phosphoric acid as the acid source to prepare pentaerythritol phosphate. By adding phosphorus pentachloride (PCl5) and ethanolamine, a nitrogen-phosphorus flame retardant was synthesized. The nitrogen-phosphorus flame retardant was used to treat polyester fabrics. The EDS results showed that the flame retardant was successfully applied to the polyester. Its flame retardancy was characterized by vertical burning and limiting oxygen index (LOI) tests. When the addition amount of the flame retardant was 100 g / L, the damaged length of the polyester was only 4.0 cm, there was no afterflame and smoldering time, there was no thick smoke during combustion, only 1 drop of molten droplet was generated, and the LOI was 30.3%, which was 58.6% higher than that of the untreated polyester. After washing 50 times, the LOI value was still higher than 30.0%. Compared with the commercially available ATP flame retardant at the same concentration, its damaged length was reduced by 28.6%, and the generation of molten droplets was significantly reduced. However, there were still problems such as the presence of molten droplets and low oxygen index, and there was still a large room for improvement.

[0006] Metal-organic frameworks (abbreviated as MOFs) are a class of porous materials with a network skeleton structure formed by the coordination bonding of metal ions and organic ligands. They have a relatively large specific surface area and good thermal stability, which have attracted the attention of researchers. In recent years, with the efforts of many researchers, many new MOFs have been prepared and great progress has been made. Currently, MOFs are widely used in the fields of hydrogen storage, separation, catalysis, flame retardancy, and adsorption.

[0007] As an organic-inorganic hybrid material, the organic ligands of MOFs can improve the compatibility between the flame retardant and the matrix, enabling the polymer to have better mechanical properties. Moreover, the organic ligands can provide flame retardant elements or groups to improve the flame retardancy efficiency. Compared with organic flame retardants, MOFs also have a large number of unsaturated metal sites, which can serve as active sites for catalytic carbonization during combustion, promoting the carbonization reaction during combustion. As a porous material, MOFs have the characteristics of a relatively large specific surface area, many internal pores, and strong adsorption capacity. They can adsorb the smoke nuclei, smoke particles, and toxic and harmful gases generated during the combustion of materials, which can significantly improve the smoke suppression performance of polymers. However, currently MOFs are applied in epoxy resins, polybutylene terephthalate / polypropylene composites, polylactic acid, thermoplastic polyurethanes, polystyrene, etc., but not in textiles.

[0008] In addition, polyester is prone to pilling during use, which shortens the service life of polyester materials and reduces the aesthetic performance of the materials.

[0009] Aiming at the problem that polyester generates molten droplets during heating and combustion, causing secondary hazards, and its low oxygen index during combustion, based on the previous research of the team, the carbon content of the flame retardant was increased, and MOFs were introduced to improve the oxygen index of polyester and avoid the generation of molten droplets. Summary of the Invention

[0010] This invention relies on the Shandong Province Small and Medium-sized Enterprise Enhancement Project "Research and Industrialization of Low-Smoke, Refractory-Dripping-Resistant Nitrogen-Phosphorus-Silicon Type Environmentally Friendly Flame Retardant 2022TSGC2552". Aiming at the defects of polyester products, such as a large number of molten droplets during combustion, causing secondary hazards, low oxygen index and generating a large amount of smoke, and the disadvantage of easy pilling during use, this invention adopts a system of N and P flame retardants combined with MOFs compounds to improve its flame-retardant char-forming property and flame-retardant oxygen index, reduce combustion molten droplets. At the same time, taking advantage of the good lubricity of esters, ammonium persulfate is used as an initiator, and ethylenediaminetetraacetic acid is used to modify the polymer amino group, so that a large number of carboxyl groups are carried in the obtained polymer. The MOFs-modified nitrogen-phosphorus flame retardant is complexed with carboxyl groups, making this flame retardant conducive to combining with anti-pilling materials and dispersing between the polyester surface and polyester fibers, preventing the polyester fibers from pilling.

[0011] Preparation of MOFs-Modified Nitrogen-Phosphorus Flame Retardant and Its Application in Polyester, including the preparation of MOFs-modified nitrogen-phosphorus flame retardant and the application of MOFs-modified nitrogen-phosphorus flame retardant in the polyester finishing process:

[0012] (1) Preparation of the nitrogen-phosphorus flame retardant intermediate pentaerythritol phosphate: Add 31.2 - 32.6 g of pentaerythritol and 47 - 50 g of phosphorus-based compound into a reaction vessel equipped with a thermometer and a stirring paddle, stir at room temperature for 1 - 2 h, raise the system temperature to 110 - 120 °C, and react for 2 - 3 h to obtain a colorless transparent liquid, namely pentaerythritol phosphate;

[0013] (2) Preparation of the nitrogen-phosphorus flame retardant: Cool the pentaerythritol phosphate obtained in step (1) to room temperature, install an exhaust gas treatment device, and add 73 - 75 g of phosphorus chloride compound in three portions within 1 - 2 h. When adding, use an alkaline solution as its absorption liquid. After adding, raise the system temperature to 45 - 50 °C, keep stirring and reacting for 1 - 2 h, cool to room temperature, and dropwise add 29 - 35 g of ethanolamine within 1 - 2 h, and continue stirring and reacting at 50 °C for 2 - 3 h to obtain a slightly yellow transparent viscous liquid, namely the product nitrogen-phosphorus flame retardant;

[0014] (3) Weigh 20 g of glycine and 40 g of 1,4-dioxane, stir and mix, adjust the pH to 8 with 30% sodium hydroxide by mass fraction, distill off water under reduced pressure, add 15.6 - 31.2 g of cyanuric chloride to the system in three portions at intervals of 15 min each, raise the reaction system temperature to 100 °C to make the reaction system reach the reflux state, and react at this temperature for 2 - 4 h, then cool naturally to room temperature. Acidify the solution to pH = 3 with 15% dilute hydrochloric acid by mass fraction, maintain stirring for 60 - 90 min, centrifuge the mixed solution, and then wash it with 50 mL of water, 30 mL of 95% alcohol and 40 mL of anhydrous methanol respectively, and dry it under vacuum to obtain cyanuric chloride flame retardant;

[0015] (4) Dissolve 12 g of the product obtained in step (3) in 60.00 mL of a mixed solution composed of N,N-dimethylacetamide and methanol in a volume ratio of 3:1. Add 1.2 - 2.4 g of aluminum sulfate, 7.5 - 11.6 g of chromium chloride, and 10 drops of ammonia water thereto. Stir the mixture for 20 min until there are no solid particles in the system. Transfer the mixed system to a polytetrafluoroethylene-lined reaction kettle and react at 110 °C for 12 - 24 h. Cool down the temperature programatically to obtain the MOFs product.

[0016] (5) Add 5.1 g of the MOFs product obtained in step (4) to step (2) and react at 70 - 90 °C for 2 - 4 h to obtain the MOFs-modified nitrogen-phosphorus-silicon flame retardant.

[0017] The phosphorus compound is any one of phosphorus pentoxide and phosphoric acid;

[0018] The phosphorus-chlorine compound is any one of phosphorus trichloride and phosphorus pentachloride.

[0019] Its application process is as follows:

[0020] (1) Cut commercially available polyester into several square cloth pieces of 25 cm × 25 cm for standby. Add 50 g of NaOH solid to a beaker containing 200 mL of distilled water in portions, stir while adding. After it is completely dissolved, add 5 g of Fit C reagent, stir evenly and transfer it to a 1000 mL volumetric flask, make up the volume with distilled water and shake well to obtain the pretreatment solution. Pour the pretreatment solution into a 5000 mL plastic beaker, place the cut fabric flat under the liquid surface, soak for 2 h, take it out, wash with water, and dry at 80 °C.

[0021] (2) Transfer the flame retardant finishing solution to a 250 mL conical flask, put the fabric from step (1) into it, place it in a water bath constant temperature oscillator and oscillate for 30 min, with the temperature at 80 °C and the rotation speed at 40 rpm. After oscillation, take out the fabric, squeeze out the water, with the liquor pickup rate being 70%. Dry it in an electric thermostatic blast drying oven at 85 °C, repeat the above operation 3 times. Bake the fabric after the fourth drying at 105 °C for 5 min to obtain the flame retardant polyester.

[0022] The preparation method of the flame retardant finishing solution: In a beaker, add 10 - 15 g of the MOFs-modified nitrogen-phosphorus flame retardant of claim 1, 3.6 g of anti-pilling material, 89 - 93 g of distilled water, 1 - 4 g of aziridine-modified isocyanate crosslinking agent, 0.5 - 1.6 g of N,N,N’,N’-tetrakis(2-hydroxypropyl)ethylenediamine, 0.2 - 1.0 g of benzylamine, and 2.8 - 3.6 g of polyester intercalation material. Wait until the reagents are completely dissolved to obtain the flame retardant finishing solution.

[0023] The preparation method of the anti-pilling material is as follows: Add 10 - 12 g of acrylamide, 14 g of allyltrimethylammonium chloride, and 11 - 15 g of ethyl acrylate to 60 g of water, then add 1.6 - 2.2 g of sodium dodecylbenzenesulfonate. After stirring and dispersing evenly, add 0.5 - 0.6 g of ammonium persulfate (dissolved or melted with 5 g of water) dropwise at 70 - 80 °C. The dropping time is 30 min, and keep the temperature at 70 - 80 °C for heat preservation reaction for 1 - 2 h. Then add 40 - 45 g of ethylenediaminetetraacetic acid and stir and react at 80 °C for 2 h to obtain a blue-light-emitting liquid, which is the anti-pilling material.

[0024] Polyester intercalation material: Add 61.2 - 64.5 g of phosphorus oxychloride to 17 g of 3,4,5-trihydroxybenzoic acid and react at 40 - 50 °C for 1 - 2 h. Then add 4.2 - 5.6 g of N-octadecyldiethanolamine and stir and react at 70 - 80 °C for 2 - 3 h. Then add 12 - 15 g of dodecatungstophosphoric acid to the system and react at 50 - 60 °C for 1 - 2 h to obtain the polyester intercalation material.

[0025] The positive effects of the present invention are as follows:

[0026] (1) Using pentaerythritol as the carbon source and phosphoric acid as the acid source, a pentaerythritol phosphate with a cage structure is prepared. Then add phosphorus pentachloride (PCl5). The hydrogen in the hydroxyl group combines with the chlorine in P-Cl, and then the amino group of ethanolamine reacts with the chlorine of the obtained compound to introduce ethanolamine into the flame retardant, supplementing the acid source, gas source, and carbon source in the system. This flame retardant contains nitrogen and phosphorus flame retardant elements and mainly exerts flame retardant effects in the gas phase and condensed phase, with low smoke and low toxicity and good flame retardant effects.

[0027] (2) Neutralize glycine to block the carboxyl group, facilitating the reaction of the amino group with the C-Cl in cyanuric chloride to form a flame retardant with a larger molecular weight. At the same time, use aluminum sulfate and chromium trichloride to complex with the carboxyl group, facilitating the dispersion of the flame retardant components around chromium trichloride and aluminum sulfate. The obtained MOFs compound has relatively strong heat resistance and can also absorb smoke, resulting in a significant reduction in the smoke of polyester, and also making polyester catalytically carbonize, greatly enhancing the charring property on the combustion surface of the polyester fabric and improving the flame retardancy of polyester. Among them, chromium and aluminum in the MOFs compound system combine with the ester groups in the polyester fabric, and the MOFs-modified nitrogen-phosphorus flame retardant is dispersed in the amorphous region of polyester and intercalated, enabling polyester to form a continuous layer during combustion and preventing polyester from melting and dripping, avoiding causing secondary hazards.

[0028] (3) Before the flame retardant treatment, the material needs to be pretreated to improve the disadvantage of low liquor pickup rate, and at the same time remove the impurities and auxiliaries on the surface of the polyester fabric for subsequent flame retardant treatment. During the finishing process, N,N,N’,N’-tetrakis(2-hydroxypropyl)ethylenediamine and benzylamine are added to enhance the rigidity of the polyester fiber system, resulting in that the strength of the fiber will not decrease significantly (and the flame retardancy will also decrease less). Aziridine-modified isocyanate is used as a crosslinking agent to combine the flame retardant components with the polyester fabric, enabling the flame retardant to exert its flame retardant effect.

[0029] (4) In the present invention, acrylamide, allyltrimethylammonium chloride, and ethyl acrylate are used to react under the dispersion of the emulsifier sodium dodecylbenzenesulfonate, and ammonium persulfate is used to initiate free radicals for the reaction. Since esters have good lubricity, ethylenediaminetetraacetic acid is used to modify the polymer amino group, so that a large number of carboxyl groups are carried in the obtained polymer. The MOFs-modified nitrogen-phosphorus flame retardant is complexed with the carboxyl groups, making this flame retardant conducive to the combination with the anti-pilling material and its dispersion between the polyester surface and polyester fibers, preventing the polyester fibers from pilling.

[0030] (5) The Fit C surface treatment agent comes from Qihe Lihou Chemical Co., Ltd., and the aziridine-modified isocyanate crosslinking agent comes from the XC-205 type of Shanghai Zelong Chemical Co., Ltd. For the chemicals without specified enterprises, as long as the main components are appropriate, they are acceptable.

[0031] (6) 3,4,5-Trihydroxybenzoic acid reacts with phosphorus oxychloride. The carboxyl group and hydroxyl group of 3,4,5-trihydroxybenzoic acid will react with the P-Cl in phosphorus oxychloride, resulting in the cleavage of the oxygen-hydrogen of the hydroxyl group or the hydroxyl group of the carboxylic acid, introducing P-Cl into the reactant and endowing the reactant with certain flame retardancy. Then, N-octadecyldiethanolamine with flexibility is introduced into the reactant, making it easy to enter the amorphous region of the polyester and causing more entanglements, so that the intercalated molecules are not easy to fall off during subsequent use and washing. At the same time, the durability of the modified polyester is improved. Dodecatungstophosphoric acid can not only catalyze the reactant to form carbon, but also continue to react with the hydroxyl group in the above reaction and be introduced into the new reaction to improve the heat resistance and flame retardancy of the compound. Detailed implementation mode

[0032] The present invention will be further described below in conjunction with examples.

[0033] Example 1

[0034] The preparation of the MOFs-modified nitrogen-phosphorus flame retardant and its application in polyester, including the preparation of the MOFs-modified nitrogen-phosphorus flame retardant and its application in the polyester finishing process. The preparation of the MOFs-modified nitrogen-phosphorus flame retardant is as follows:

[0035] (1) Preparation of the nitrogen-phosphorus flame retardant intermediate pentaerythritol phosphate: Add 31.2 g of pentaerythritol and 47 g of phosphorus pentoxide into a reaction vessel equipped with a thermometer and a stirring paddle. Stir at room temperature for 1 h, then raise the temperature of the system to 110 °C and react for 2 h to obtain a colorless transparent liquid, namely pentaerythritol phosphate;

[0036] (2) Preparation of the nitrogen-phosphorus flame retardant: Cool the pentaerythritol phosphate obtained in step (1) to room temperature, install an exhaust gas treatment device, and add 73 g of phosphorus trichloride in three portions within 1 h, with an interval of 20 min each time. Raise the temperature of the system to 45 °C, keep stirring and reacting for 1 h, then cool to room temperature. Dropwise add 29 g of ethanolamine within 1 h (it can also be added in portions, with an interval of 20 minutes each time, for 3 times, the same below), and continue stirring and reacting at 50 °C for 2 h to obtain a slightly yellow transparent viscous liquid, namely the product nitrogen-phosphorus flame retardant;

[0037] (3) Weigh 20 g of glycine and 40 g of 1,4-dioxane, stir and mix them, adjust the pH to 8 with 30% sodium hydroxide by mass fraction, distill off water under reduced pressure, add 15.6 g of cyanuric chloride to the system in three portions, with an interval of 15 min each time. Raise the temperature of the reaction system to 100 °C to make the reaction system reach the reflux state, and react at this temperature for 2 h. Naturally cool to room temperature, acidify the solution to pH = 3 with 15% hydrochloric acid by mass fraction, maintain stirring for 60 min, centrifuge the mixed solution, and then wash it with 50 mL of water, 30 mL of 95% alcohol, and 40 mL of anhydrous methanol respectively, and dry it under vacuum to obtain the cyanuric chloride flame retardant;

[0038] (4) Dissolve 12 g of the product obtained in step (3) in 60.00 mL of a mixed solution composed of N,N-dimethylacetamide and methanol in a volume ratio of 3:1. Add 1.2 g of aluminum sulfate, 7.5 g of chromium chloride, and 10 drops of ammonia water to it, stir the mixed solution for 20 min until there are no solid particles in the system. Transfer the mixed system to a polytetrafluoroethylene-lined reaction kettle and react at 110 °C for 12 h, and then cool down step by step to obtain the MOFs product.

[0039] (5) Add 5.1 g of the MOFs product obtained in step (4) to step (2), and react at 70 °C for 2 h to obtain the MOFs-modified nitrogen-phosphorus-silicon flame retardant.

[0040] Its application process is as follows:

[0041] (1) Cut commercially available polyester into several square cloth pieces of 25 cm × 25 cm for standby. Gradually add 50 g of solid NaOH to a beaker containing 200 mL of distilled water. Add and stir simultaneously. After it is completely dissolved, add 5 g of Fit C reagent, stir evenly and transfer it to a 1000 mL volumetric flask. Make up the volume with distilled water and shake well to obtain a pretreatment solution. Pour the pretreatment solution into a 5000 mL plastic beaker. Place the cut fabric flat under the liquid surface, soak for 2 h, take it out, wash with water, and dry at 80 °C.

[0042] (2) Transfer the flame retardant finishing solution to a 250 mL conical flask, immerse the fabric from step (1), place it in a water bath constant temperature oscillator and oscillate for 30 min, with the temperature at 80 °C and the rotation speed at 40 rpm. After oscillation, take out the fabric and squeeze out the moisture. The liquor ratio is 70%. Dry it in an electrothermal constant temperature blast drying oven at 85 °C. Repeat the above operation 3 times. Bake the fabric after the fourth drying at 105 °C for 5 min to obtain the flame retardant polyester.

[0043] The preparation method of the flame retardant finishing solution: In a beaker, add 10 g of the MOFs modified nitrogen-phosphorus flame retardant of claim 1, 3.6 g of the anti-pilling material, 89 g of distilled water, 1 g of aziridine modified isocyanate crosslinking agent, 0.5 g of N,N,N’,N’-tetrakis(2-hydroxypropyl)ethylenediamine, 0.2 g of benzylamine, and 2.8 g of polyester intercalation material. Wait until the reagents are completely dissolved to obtain the flame retardant finishing solution.

[0044] The preparation method of the anti-pilling material: Add 10 g of acrylamide, 14 g of allyltrimethylammonium chloride, and 11 g of ethyl acrylate to 60 g of water, and then add 1.6 g of sodium dodecylbenzenesulfonate. After stirring and dispersing evenly, add dropwise at 70 °C, add 0.5 g of ammonium persulfate (dissolved or diluted with 5 g of water, the same below), the dropping time is 30 min, keep the temperature at 70 °C and react for 1 h. Then add 40 g of ethylenediaminetetraacetic acid and stir and react at 80 °C for 2 h to obtain a blue-light-emitting liquid, which is the anti-pilling material.

[0045] Polyester intercalation material: Add 61.2 g of phosphorus oxychloride to 17 g of 3,4,5-trihydroxybenzoic acid and react at 40 °C for 1 h. Then add 4.2 g of N-octadecyldiethanolamine and stir and react at 70 °C for 2 h. Then add 12 g of dodecatungstophosphoric acid to the system and react at 50 °C for 1 h to obtain the polyester intercalation material.

[0046] Example Two

[0047] The preparation of the MOFs modified nitrogen-phosphorus flame retardant and its application in polyester, including the preparation of the MOFs modified nitrogen-phosphorus flame retardant and the application of the MOFs modified nitrogen-phosphorus flame retardant in the polyester finishing process:

[0048] (1) Preparation of pentaerythritol phosphate, an intermediate of nitrogen-phosphorus flame retardant: Add 32.6 g of pentaerythritol and 50 g of phosphoric acid into a reaction vessel equipped with a thermometer and a stirring paddle, stir at room temperature for 2 h, raise the temperature of the system to 120 °C, and react for 3 h to obtain a colorless transparent liquid, namely pentaerythritol phosphate;

[0049] (2) Preparation of nitrogen-phosphorus flame retardant: Cool the pentaerythritol phosphate obtained in step (1) to room temperature, install an exhaust gas treatment device, add 75 g of phosphorus pentachloride in three portions over 2 h, with an interval of 40 min between each addition. During the addition, use an alkaline solution as the absorption liquid. After the addition is completed, raise the temperature of the system to 50 °C, keep stirring and reacting for 2 h, cool to room temperature, add 35 g of ethanolamine dropwise within 2 h, and continue stirring and reacting at 50 °C for 3 h to obtain a slightly yellow transparent viscous liquid, namely the product nitrogen-phosphorus flame retardant;

[0050] (3) Weigh 20 g of glycine and 40 g of 1,4-dioxane, stir and mix them, adjust the pH to 8 with 30% sodium hydroxide by mass fraction, distill off water under reduced pressure, add 31.2 g of cyanuric chloride to the system in three portions, with an interval of 15 min between each addition. Raise the temperature of the reaction system to 100 °C to make the reaction system reach the reflux state, and react at this temperature for 4 h. Naturally cool to room temperature, acidify the solution to pH = 3 with 15% hydrochloric acid by mass fraction, maintain stirring for 90 min, centrifuge the mixture, and then wash it with 50 mL of water, 30 mL of 95% alcohol, and 40 mL of anhydrous methanol respectively, and dry it under vacuum to obtain cyanuric chloride flame retardant;

[0051] (4) Dissolve 12 g of the product obtained in step (3) in 60.00 mL of a mixed solution composed of N,N-dimethylacetamide and methanol in a volume ratio of 3:1. Add 2.4 g of aluminum sulfate, 11.6 g of chromium chloride, and 10 drops of ammonia water to it, stir the mixture for 20 min until there are no solid particles in the system, transfer the mixed system to a polytetrafluoroethylene-lined reaction kettle, and react at 110 °C for 24 h, and then cool down step by step to obtain the MOFs product.

[0052] (5) Add 5.1 g of the MOFs product obtained in step (4) to step (2), and react at 90 °C for 4 h to obtain the MOFs-modified nitrogen-phosphorus-silicon flame retardant.

[0053] Its application process is as follows:

[0054] (1) Cut commercially available polyester into several square cloth pieces of 25 cm × 25 cm for standby. Add 50 g of solid NaOH to a beaker containing 200 mL of distilled water in portions. Stir while adding. After it is completely dissolved, add 5 g of Fit C reagent, stir evenly, transfer it to a 1000 mL volumetric flask, make up the volume with distilled water, shake well to obtain a pretreatment solution. Pour the pretreatment solution into a 5000 mL plastic beaker, place the cut fabric flat under the liquid surface, soak for 2 h, take it out, wash with water, and dry at 80 °C;

[0055] (2) Transfer the flame retardant finishing solution to a 250 mL conical flask, immerse the fabric from step (1), place it in a water bath thermostatic oscillator and oscillate for 30 min, with the temperature at 80 °C and the rotation speed at 40 rpm. After oscillation, take out the fabric, squeeze out the water, and the liquor pickup rate is 70%. Dry it in an electrothermal constant temperature blast drying oven at 85 °C. Repeat the above operation 3 times. Bake the fabric after the fourth drying at 105 °C for 5 min to obtain the flame retardant polyester.

[0056] The preparation method of the flame retardant finishing solution: In a beaker, add 15 g of the MOFs modified nitrogen-phosphorus flame retardant in claim 1, 3.6 g of the anti-pilling material, 93 g of distilled water, 4 g of aziridine modified isocyanate crosslinking agent, 1.6 g of N,N,N’,N’-tetrakis(2-hydroxypropyl)ethylenediamine, 1.0 g of benzylamine, and 3.6 g of polyester intercalation material. Wait until the reagents are completely dissolved to obtain the flame retardant finishing solution.

[0057] The preparation method of the anti-pilling material: Add 12 g of acrylamide, 14 g of allyltrimethylammonium chloride, and 15 g of ethyl acrylate to 60 g of water, then add 2.2 g of sodium dodecylbenzenesulfonate. After stirring and dispersing evenly, add dropwise at 80 °C, add 0.6 g of ammonium persulfate dropwise, with the dropping time of 30 min, keep the temperature at 80 °C for 2 h of reaction, then add 45 g of ethylenediaminetetraacetic acid, and stir and react at 80 °C for 2 h to obtain a liquid emitting blue light, which is the anti-pilling material.

[0058] Polyester intercalation material: Add 64.5 g of phosphorus oxychloride to 17 g of 3,4,5-trihydroxybenzoic acid, react at 50 °C for 2 h, then add 5.6 g of N-octadecyldiethanolamine, stir and react at 80 °C for 3 h, and then add 15 g of dodecatungstophosphoric acid to the system, react at 60 °C for 2 h to obtain the polyester intercalation material.

[0059] Example Three

[0060] The preparation and application of the MOFs modified nitrogen-phosphorus flame retardant in polyester, including the preparation of the MOFs modified nitrogen-phosphorus flame retardant, the application of the MOFs modified nitrogen-phosphorus flame retardant in the polyester finishing process, and the preparation method of the MOFs modified nitrogen-phosphorus flame retardant is as follows:

[0061] (1) Preparation of the nitrogen-phosphorus flame retardant intermediate pentaerythritol phosphate: Add 31.9 g of pentaerythritol and 48.5 g of phosphorus pentoxide into a reaction vessel equipped with a thermometer and a stirring paddle. Stir at room temperature for 1.5 h, then raise the system temperature to 115 °C and react for 2.5 h to obtain a colorless transparent liquid, namely pentaerythritol phosphate;

[0062] (2) Preparation of the nitrogen-phosphorus flame retardant: Cool the pentaerythritol phosphate obtained in step (1) to room temperature, install an exhaust gas treatment device, and add 74 g of phosphorus trichloride in three portions within 1.5 h, with an interval of 30 min between each addition. During the addition, use an alkaline solution as the absorption liquid. After the addition is completed, raise the system temperature to 45 °C, keep it warm and stir for 1.5 h, then cool to room temperature. Dropwise add 32 g of ethanolamine within 1.5 h and continue to stir and react at 50 °C for 2.5 h to obtain a slightly yellow transparent viscous liquid, namely the product nitrogen-phosphorus flame retardant;

[0063] (3) Weigh 20 g of glycine and 40 g of 1,4-dioxane, stir and mix them, adjust the pH to 8 with 30% sodium hydroxide by mass fraction, distill off water under reduced pressure, add 23.4 g of cyanuric chloride to the system in three portions, with an interval of 15 min between each addition. Raise the reaction system temperature to 100 °C to make the reaction system reach the reflux state, and react at this temperature for 3 h. Naturally cool to room temperature, acidify the solution to pH = 3 with 15% dilute hydrochloric acid by mass fraction, maintain stirring for 75 min, centrifuge the mixed solution, and then wash it with 50 mL of water, 30 mL of 95% alcohol, and 40 mL of anhydrous methanol respectively, and dry it under vacuum to obtain the cyanuric chloride flame retardant;

[0064] (4) Dissolve 12 g of the product obtained in step (3) in 60.00 mL of a mixed solution composed of N,N-dimethylacetamide and methanol in a volume ratio of 3:1. Add 1.8 g of aluminum sulfate, 9.5 g of chromium chloride, and 10 drops of ammonia water to it, stir the mixed solution for 20 min until there are no solid particles in the system, transfer the mixed system to a polytetrafluoroethylene-lined reaction kettle, and react at 110 °C for 18 h, and then cool down step by step to obtain the MOFs product;

[0065] (5) Add 5.1 g of the MOFs product obtained in step (4) to step (2), and react at 80 °C for 3 h to obtain the MOFs-modified nitrogen-phosphorus-silicon flame retardant.

[0066] Its application process is as follows:

[0067] (1) Cut commercially available polyester into several 25 cm × 25 cm square pieces for later use. Add 50 g of NaOH solid in a beaker containing 200 mL of distilled water in portions while stirring. After the solid is completely dissolved, add 5 g of Fit C reagent and stir evenly. Transfer the mixture to a 1000 mL volumetric flask, dilute to volume with distilled water, and shake well to obtain a pretreatment solution. Pour the pretreatment solution into a 5000 mL plastic beaker, place the cut fabric flatly under the liquid surface, soak for 2 h, take it out, wash it with water, and dry it at 80°C.

[0068] (2) The flame retardant finishing liquid is transferred to a 250 mL conical flask, immersed in the fabric prepared in step (1), and placed in a water bath constant temperature oscillator for 30 min at a temperature of 80° C. and a rotation speed of 40 rpm. After the oscillation is completed, the fabric is taken out and the water is squeezed out. The squeeze-out rate is 70%, and the fabric is dried in an electric constant temperature blast drying oven at 85° C. The above operation is repeated 3 times. The fabric after the fourth drying is baked at 105° C. for 5 min to obtain the flame retardant polyester.

[0069] The preparation method of the flame retardant finishing liquid is as follows: 12.5g of the MOFs-modified nitrogen-phosphorus flame retardant of claim 1, 3.6g of anti-pilling material, 91g of distilled water, 2.5g of aziridine-modified isocyanate crosslinking agent, 1.05g of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine, 0.6g of benzylamine, and 3.2g of polyester intercalation material are placed in a beaker, and the flame retardant finishing liquid is obtained after the reagents are completely dissolved.

[0070] The preparation method of the anti-pilling material is as follows: 11g of acrylamide, 14g of allyltrimethylammonium chloride, and 13g of ethyl acrylate are added to 60g of water, and then 1.9g of sodium dodecylbenzenesulfonate is added. After stirring and dispersing evenly, 0.55g of ammonium persulfate is added dropwise at 75°C for 30min, and the reaction is kept at 75°C for 1.5h, and then 42.5g of ethylenediaminetetraacetic acid is added. The reaction is stirred at 80°C for 2h to obtain a blue-light-emitting liquid, which is the anti-pilling material.

[0071] Polyester intercalation material: Add 62.9 g of phosphorus oxychloride to 17 g of 3,4,5-trihydroxybenzoic acid, react at 45°C for 1.5 h, then add 4.8 g of N-octadecyl diethanolamine, stir and react at 75°C for 2.5 h. Then add 13.5 g of dodecaphosphotungstic acid to the system, react at 55°C for 1.5 h to obtain the polyester intercalation material.

[0072] Pilling grade: According to GB / T 4802.1-2008 "Test for Pilling of Textile Fabrics" standard, the washing process of flame-retardant polyester fabrics is as follows: the experiment simulates the environment of household machine washing, and uses a small washing machine to wash the samples in batches for 50 times, adding 3 drops of laundry detergent each time, washing for 12 minutes, rinsing for 3 minutes, dehydrating, taking out and drying. After washing 50 times, the fabric is naturally dried to obtain the flame-retardant polyester after washing.

[0073] The flame-retardant polyester fabrics prepared according to the embodiments of the present invention and the polyester fabrics treated with the existing commercially available flame retardant nitrogen-phosphorus flame retardant ATP were respectively detected and compared with the effects of the master's thesis of Wang Qi of our team.

[0074] According to GB / T 8746-2009 "Textiles - Burning behavior - Determination of ease of ignition of vertically oriented specimens", the flame-retardant treated fabric was cut into required sizes and placed in a thermostatic and humidistatic chamber (controlled temperature 21°C, humidity 65%) for testing. The fabric was fixed on a fixture, and a CZF-3 horizontal and vertical burning tester produced by Nanjing Shangyuan Analytical Instrument Co., Ltd. was used for vertical burning test. Observe the burning situation of the specimen, record the flaming burning time and non-flaming burning time of the specimen, and measure its char length.

[0075] The limiting oxygen index refers to the lowest oxygen ratio required to support the specimen to just completely burn within 3 minutes when the specimen is ignited in an atmosphere of nitrogen-oxygen mixed gas. Generally speaking, the higher the value of the limiting oxygen index, the higher the oxygen concentration required for the specimen to burn, that is, the more difficult it is for the specimen to burn.

[0076] According to TB / T 2919-1998 "Test method for oxygen index of fabric combustion", the flame-retardant treated fabric was cut into a size of 5 cm × 15 cm and placed in a thermostatic and humidistatic chamber (temperature set at 21°C, humidity set at 60%) for more than 24 hours for testing. The specimen was fixed in a fixture, covered with a glass cover, ignited above the specimen to ensure that the specimen could burn evenly from top to bottom, and then the ignition source was removed.

[0077] The char residue rate refers to the percentage of the mass of the remaining sample after the material is burned at high temperature to the mass of the original sample, which is one of the evaluation indexes of the flame retardancy of the material. Generally speaking, the higher the value of the char residue rate, the better the flame retardant effect of the material.

[0078] The sample was placed in an electrothermal constant temperature forced air drying oven and dried to a constant weight. Weigh about 1 g of the sample to be tested into a 30 mL ceramic crucible, record the mass of the empty crucible as m0 and the mass of the sample as m. Place the crucible in a muffle furnace and heat it from room temperature to 200°C at a heating rate of 10°C / min and hold for 30 minutes. Take out the sample, cool it to room temperature in a desiccator, and weigh it. Repeat the above operation. Starting from 200°C, heat it at a heating rate of 10°C / min to 500°C to obtain the char residue rate.

[0079] Record the total mass of the crucible and the remaining sample after each cooling and taking out as mi (i = 1, 2, 3,...).

[0080]

[0081] ​The testing instrument uses the Sansi Zongheng UTM4103 universal testing machine. The testing standard refers to GB / T 3923.1-2013 "Textiles - Tensile properties of fabrics - Part 1: Determination of maximum force and elongation at break (strip method)". The original gauge length is 200 mm, and the tensile speed is 100 mm / min.

[0082] Smoke suppression performance: According to the ISO5659 standard, the FTT0064 test chamber is used to conduct flameless heating on the fabric before and after finishing. The heating temperature is 560 °C, the time is 700 s, and the radiation power is 25 kw / m 2 . The sample size is 80×80 mm 2 , and the maximum combustion smoke is taken for comparison (smoke suppression).

[0083] Table 1 Comparison of the properties of flame-retardant treated polyester fabrics

[0084] Project Example 1 Example 2 Example 3 Oxygen index / ℃ 38.2 39.3 39.4 Tensile strength / Mpa (warp) 43.26 42.58 41.32 Maximum elongation at break / % (warp) 28.25 27.38 27.68 Maximum force / N (warp) 326.28 325.41 328.24 Afterflame time / s 0 0 0 Smoldering time / s 0 0 0 Damaged length / cm 1.6 1.2 1.5 Residual carbon rate at 500℃ / % 23.68 29.56 31.26 Smoke suppression (maximum) 12.52 13.45 11.25 Dripping phenomenon No dripping No dripping No dripping Pilling resistance grade / level 4.5 5.0 4.5

[0085] As can be seen from Table 1, in Examples 1-3 of the present invention, no dripping occurs, the afterflame time and the smoldering time are both 0, and its limiting oxygen index also exceeds the previous achievements of the team and the best polyester flame retardant ATP in the market. The more the pilling resistance level, the better (take the average value of several tests, set half a level).

[0086] Table 2 Comparison of the properties of flame-retardant treated polyester fabrics

[0087]

[0088] Referring to the relevant part of the master's thesis of Wang Qi in the early stage of the team, there are appropriate differences in the data compared with the previous ones. Taking the thesis as the standard, combined with Table 1, it shows that the previous improvement plan of the team is superior to the effects of the previous flame-retardant polyester of the team and the ATP flame retardant in the market.

[0089] Table 3 Properties of some materials not added (studied with Example 2)

[0090]

[0091]

[0092] In Table 3, more dripping means that there are more than 10 dripping droplets in the combustion test sample, and less means that there are no more than 5-9 dripping droplets. It can be found from Table 3 that the properties of polyester intercalation materials, N-octadecyldiethanolamine, ethylenediaminetetraacetic acid, MOFs-modified nitrogen-phosphorus flame retardant, chromium chloride, etc. not added all decrease to varying degrees.

[0093] Taking Example 2 as an example, after 50 times of water washing, the oxygen index of polyester is 34.2, and the decrease range is about 10%. All the above test data are tested in the warp direction of polyester unless otherwise specified. The char residue rate of the MOFs-modified nitrogen-phosphorus flame retardant is 71.24 (taking Example 2 as an example).

Claims

1. Preparation method of MOFs-modified nitrogen-phosphorus flame retardant, characterized in that: (1) Preparation of nitrogen-phosphorus flame retardant intermediate pentaerythritol phosphate: Add 31.2 - 32.6 g of pentaerythritol and 47 - 50 g of phosphorus-based compound into a reaction vessel equipped with a thermometer and a stirring paddle, stir at room temperature for 1 - 2 h, raise the system temperature to 110 - 120 °C, and react for 2 - 3 h to obtain a colorless transparent liquid, namely pentaerythritol phosphate; (2) Preparation of nitrogen-phosphorus flame retardant: Cool the pentaerythritol phosphate obtained in step (1) to room temperature, install an exhaust gas treatment device, add 73 - 75 g of phosphorus chloride compound in three portions within 1 - 2 h. When adding, use an alkaline solution as its absorption liquid. After adding, raise the system temperature to 45 - 50 °C, keep stirring and reacting for 1 - 2 h, cool to room temperature, dropwise add 29 - 35 g of ethanolamine within 1 - 2 h, and continue stirring and reacting at 50 °C for 2 - 3 h to obtain a slightly yellow transparent viscous liquid, namely the product nitrogen-phosphorus flame retardant; (3) Weigh 20 g of glycine and 40 g of 1,4-dioxane, stir and mix, adjust the pH to 8 with 30% sodium hydroxide by mass fraction, distill off water under reduced pressure, add 15.6 - 31.2 g of cyanuric chloride to the system in three portions at intervals of 15 min, raise the reaction system temperature to 100 °C to make the reaction system reach the reflux state, and react at this temperature for 2 - 4 h, cool naturally to room temperature, acidify the solution to pH = 3 with 15% dilute hydrochloric acid by mass fraction, maintain stirring for 60 - 90 min, centrifuge the mixed solution, and then wash it with 50 mL of water, 30 mL of 95% alcohol and 40 mL of anhydrous methanol respectively, and dry it under vacuum to obtain cyanuric chloride flame retardant; (4) Dissolve 12 g of the product obtained in step (3) in 60.00 mL of a mixed solution composed of N,N-dimethylacetamide and methanol in a volume ratio of 3:1, add 1.2 - 2.4 g of aluminum sulfate, 7.5 - 11.6 g of chromium chloride and 10 drops of ammonia water to it, stir the mixed solution for 20 min until there are no solid particles in the system, transfer the mixed system to a polytetrafluoroethylene-lined reaction kettle, react at 110 °C for 12 - 24 h, and cool down step by step to obtain MOFs product; (5) Add 5.1 g of the MOFs product obtained in step (4) to step (2), and react at 70 - 90 °C for 2 - 4 h to obtain MOFs-modified nitrogen-phosphorus-silicon flame retardant.

2. The preparation method of MOFs-modified nitrogen-phosphorus flame retardant according to claim 1, wherein the phosphorus-based compound is any one of phosphorus pentoxide and phosphoric acid.

3. The preparation method of MOFs-modified nitrogen-phosphorus flame retardant according to claim 1, wherein the phosphorus chloride compound is any one of phosphorus trichloride and phosphorus pentachloride.

4. Application of the MOFs-modified nitrogen-phosphorus flame retardant prepared by the preparation method according to any one of claims 1 - 3 in polyester, and its application process is as follows: (1)Cut commercially available polyester into several square cloth pieces of 25 cm×25 cm for standby. Add 50 g of solid NaOH to a beaker containing 200 mL of distilled water in portions. Stir while adding. After it is completely dissolved, add 5 g of Fite C reagent, stir evenly, transfer it to a 1000 mL volumetric flask, make up the volume with distilled water, shake well to obtain a pretreatment solution. Pour the pretreatment solution into a 5000 mL plastic beaker, place the cut fabric flat under the liquid surface, soak for 2 h, take it out, wash with water, and dry at 80 °C; (2)Transfer the flame retardant finishing solution to a 250 mL conical flask, add the fabric from step (1), place it in a water bath constant temperature oscillator and oscillate for 30 min, the temperature is 80 °C, and the rotation speed is 40 rpm. After oscillation, take out the fabric, squeeze out the water, the liquor ratio is 70%, and dry it in an electrothermal constant temperature forced air drying oven at 85 °C. Repeat the above operation 3 times. Bake the fabric after the fourth drying at 105 °C for 5 min to obtain the flame retardant polyester; Among them, the preparation method of the flame retardant finishing solution: In a beaker, 10 - 15 g of the MOFs modified nitrogen-phosphorus flame retardant of claim 1, 3.6 g of anti-pilling material, 89 - 93 g of distilled water, 1 - 4 g of aziridine modified isocyanate crosslinking agent, 0.5 - 1.6 g of N,N,N’,N’-tetrakis(2-hydroxypropyl)ethylenediamine, 0.2 - 1.0 g of benzylamine, 2.8 - 3.6 g of polyester intercalation material. Wait for the reagents to be completely dissolved to obtain the flame retardant finishing solution; The preparation method of the anti-pilling material: Add 10 - 12 g of acrylamide, 14 g of allyltrimethylammonium chloride, and 11 - 15 g of ethyl acrylate to 60 g of water, then add 1.6 - 2.2 g of sodium dodecylbenzenesulfonate. After stirring and dispersing evenly, add 0.5 - 0.6 g of ammonium persulfate dropwise at 70 - 80 °C, the dropping time is 30 min, keep the temperature at 70 - 80 °C and react for 1 - 2 h, then add 40 - 45 g of ethylenediaminetetraacetic acid, and stir and react at 80 °C for 2 h to obtain a blue-light-emitting liquid, which is the anti-pilling material; Polyester intercalation material: Add 61.2 - 64.5 g of phosphorus oxychloride to 17 g of 3,4,5-trihydroxybenzoic acid, react at 40 - 50 °C for 1 - 2 h, then add 4.2 - 5.6 g of N-octadecyldiethanolamine, stir and react at 70 - 80 °C for 2 - 3 h, then add 12 - 15 g of dodecatungstophosphoric acid to the system, and react at 50 - 60 °C for 1 - 2 h to obtain the polyester intercalation material.

Citation Information

Patent Citations

  • Durable polyester flame retardant and preparation method and application thereof

    CN113089330A

  • A high-elasticity flame-retardant polyester fabric and its preparation method

    CN114808190B

  • Flame retardant catalyst of metal organic frame complex and preparation method thereof

    CN106046389A

  • Nitrogen-phosphorus synergistic Al-based MOFs flame retardant as well as preparation method and application thereof

    CN113174057A